Femtosecond laser direct writing of microholes on roughened ZnO for output power enhancement of InGaN light-emitting diodes - Zang, Zhigang; Zeng, Xiaofeng; Du, Jihe; Wang, Ming; Tang, Xiaosheng (Optics letters, 2016)
A significant enhancement of light extraction efficiency from InGaN light-emitting diodes (LEDs) with microhole arrays and roughened ZnO was experimentally demonstrated. The roughened ZnO was fabricated using an Ar and H plasma treatment of ZnO films pre-coated on a p-GaN layer. When followed by a femtosecond laser direct writing technique, a periodic array of microholes could be added to the surface. The diameter of the microhole was varied by changing the output power of the femtosecond laser. Compared to conventional LEDs on the same wafer, the output power of LEDs with roughened ZnOs and a microhole (diameter of 2 μm) array was increased by 58.4% when operated with an injection current of 220 mA. Moreover, it was found that LEDs fabricated with roughened ZnO and the microhole array had similar current-voltage (I-V) characteristics to those of conventional LEDs and no degrading effect was observed.